Vegetables suitable for association with subsistence maize and beans in the highlands of Guatemala - Kass, D.C.L. (1981)
Ilus. 4 figuras, 6 tablas, 21 ref. Sum. (Es) También en microficha *IICA, Turrialba (Costa Rica).